2006
DOI: 10.1021/jf051742k
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Seven Organosulfur Compounds in Garlic by High-Performance Liquid Chromatography

Abstract: The properties of garlic (Allium sativum L.) are attributed to organosulfur compounds. Although these compounds change during cultivation and storage, there is no report of their simultaneous analysis. Here, a newly developed analytical method with a rapid and simple sample preparation to determine four sulfoxides and three gamma-glutamyl peptides in garlic is reported. All garlic samples were simply extracted with 90% methanol solution containing 0.01 N hydrochloric acid and prepared for analysis. Alliin, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 28 publications
4
54
0
2
Order By: Relevance
“…Therefore, degradation of S-alk(en)yl-L-cysteines in raw onions was due to heating, and subsequent conversion to ACSOs was verified (19). Increased level of ACSOs indicated that γ-glutamyl peptides were converted into corresponding sulfoxides by γ-glutamyl peptidase and oxidase (15). Changes in ACSOs compositions were different in heat-treated onions.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, degradation of S-alk(en)yl-L-cysteines in raw onions was due to heating, and subsequent conversion to ACSOs was verified (19). Increased level of ACSOs indicated that γ-glutamyl peptides were converted into corresponding sulfoxides by γ-glutamyl peptidase and oxidase (15). Changes in ACSOs compositions were different in heat-treated onions.…”
Section: Resultsmentioning
confidence: 91%
“…The ACSOs precursors S-alk(en)yl-L-cysteines are produced from γ-L-glutamyl-S-(trans-1-propenyl)-L-cysteines by γ-glutamyl peptidase, and an oxidase chemically converts S-alk(en)yl-L-cysteines to ACSOs (15,16). Although ACSOs are found at low levels in raw onions, the level was increased during domestic processing of steaming, frying, and microwave cooking.…”
Section: Resultsmentioning
confidence: 99%
“…One peeled onion bulb (harvested in 2007 in Hokkaido, Japan) was divided vertically into eight equal portions: three were analyzed immediately as a raw material, three were freeze-dried to be evaluated as described in this paper, and the remaining two were measured for their raw moisture contents. To evaluate the raw material, the onion bulbs were divided vertically again in half (1/16 of whole bulb, about 12 g each), and three halves were immediately extracted with 70 mL methanol-0.01 mol/L hydrochloric acid (90:10, v/v) for 10 min using a food blender after division (Ichikawa et al, 2006a). The obtained raw homogenates were diluted to 100 mL with the extract solutions used to wash the apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the chemical constituents present in Allium sativum (garlic) are known (Amagase, 2006). From the garlic skin, the part used in 'Tira-capeta', were isolated phenylpropanoids (Ichikawa et al, 2003(Ichikawa et al, , 2006 and flavonoids (Stajner et al, 2006). Of the two remaining plants, Anemopaegma arvense ('alecrimdo-norte') and Hyptis cana ('hortelã-da-várzea'), there are no phytochemical data in the literature, but we suppose that they possess tannins, flavonoids and saponins, since they are the major constituents of ETC.…”
Section: Catalepsy Testmentioning
confidence: 99%